Imagens e estratégias de poder: a construção midiática dos territórios do medo - Jesus, Adriano Miranda Vasconcellos de (2014)
This research studies the fear, an abstract and diffuse sense as the engine for a new symbolic cartography of the city, and also a revelator of the performance of power. Understand the social perception that arises from the performance of technical means is to recover images created by the complex relationship between media and its devices. The object of the research lies in the study of fear which arises from the communicative environment spectacularly ordained by the mass media and dissolved in everyday culture. Five episodes are analyzed: Fire in the slums of São Paulo, police killings in civilian operations, implementation of community policing, resumption of the Complexo do Alemão and OperaçãoSaturação. From the methodological point of view, the events are understood as events which suggest vectors of analysis as a recurring impact to its manifestations. These vectors of images are identified as: shift, visualizing, emptiness, sanitize and functionalize. They appear as signatures of thr archeology of fear in the city. Considering conceptual matrices observed in biopolitics, the study of fear induced by the media leads us to the reading of Hobbes, Spinoza and Tocqueville from which it was possible to understand the policy established in cities across visual media strategies. In addition to the authors mentioned, the theoretical basis of the work relies on fundamental concepts proposed by Michael Foucault: governmentality, happenings and archeology of knowledge, also through visual media as a communicative device supported in the work of Agamben. Authors like Delumeau, Castoriadis, and RancièreMafessoli assist us in understanding the fear and its extensions